Ethnoscience learning: how do teacher implementing to increase scientific literacy in junior high school - Jufrida Jufrida; Wawan Kurniawan; Fibrika Rahmat Basuki (International Journal of Evaluation and Research in Education (IJERE), 2024)
Ethnoscience learning is an activity that connects local wisdom or cultural with science concepts. A mixed method study with an embedded design was used to describe how do teachers apply ethnoscience learning to increase scientific literacy. A total of 90 students grade 8th in District Muaro Jambi were involved in this study consisted of three classes. In-depth interviews and observations were conducted to collect qualitative data. The observation was used to determine the suitability of learning with the lesson plan. Deep interviews were used to explore teacher and student experiences in implementing ethnoscience learning. A teacher and three students were randomly selected as key informants. The quantitative data were collected by scientific literacy test that consisted of ten multiple choices. It has been tested for validity and reliability. The result of the reliability test is 0.85 with a very high category. Increase in scientific literacy is measured by normalized gain (N-gain). The analysis of variance (ANOVA) test was applied to determine scientific literacy differences between groups. Ethnoscience learning had been implemented by teacher in three different class on topic simple machines. It was designed by integrating local wisdom as a context for finding scientific concepts. The learning was designed by following a discovery model. The implementation of ethnoscience learning can increase scientific literacy with medium category. There was no significant difference between three classes.